A comparison of front-line oral anticoagulants for the treatment of non-valvular atrial fibrillation: effectiveness and safety of direct oral anticoagulants in the FANTASIIA registry. (13th August 2022) - Esteve-Pastor, María Asunción; Rivera-Caravaca, José Miguel; Ruiz-Ortiz, Martín; Muñiz, Javier; Roldán-Rabadán, Inmaculada; Otero, Déborah; López-Gálvez, Raquel; Cequier, Ángel; Bertomeu-Martínez, Vicente; Badimón, Lina; Anguita, Manuel; Lip, Gregory Y.H.; et al.
ABSTRACT: Introduction: For a long time, vitamin K antagonists (VKA) were the only oral anticoagulation therapy available to reduce adverse events in atrial fibrillation (AF) patients. Direct-acting oral anticoagulants (DOAC) are at least as effective and safe as VKA with few drug interactions, rapid onset, and short half-life. Four DOACs, dabigatran, apixaban, rivaroxaban, and edoxaban, have demonstrated efficacy and safety for treatment in AF patients. Areas Covered: The purpose of this review article is to analyze the current evidence in clinical trials and in real-world populations and performed a new analysis with the estimated effect of those DOACs over the VKA population from the FANTASIIA registry. Expert Opinion: In the absence of randomized, controlled head-to-head comparisons between DOACs, high-quality observational data can provide useful information on the comparative effectiveness of DOACs. Current clinical guidelines recommend the management of oral anticoagulation in AF patients with DOACs over VKA for stroke prevention; however, many guidelines generally do not suggest a specific DOAC choice in clinical practice. The revised evidence in this manuscript and our real experience reflects that apixaban and dabigatran show the best efficacy and safety profile.